2014
DOI: 10.1177/2325967114561962
|View full text |Cite
|
Sign up to set email alerts
|

Structural Properties of the Native Ligamentum Teres

Abstract: Background:A majority of studies investigating the role of the ligamentum teres (LT) have focused primarily on anatomical and histological descriptions. To date, however, the structural properties of the LT have yet to be fully elucidated.Purpose:To investigate the structural properties of the native LT in a human cadaveric model.Study Design:Descriptive laboratory study.Methods:A total of 12 human cadaveric hemipelvises (mean age, 53.6 years; range, 34-63 years) were dissected free of all extra-articular soft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 27 publications
2
30
0
1
Order By: Relevance
“…There were no significant sex or side differences between any of these ligament dimensions, in spite of ligament injuries being more commonly reported on the right side, and in females (Byrd and Jones, ; Haviv and O'Donnell, ; Amenabar and O'Donnell, ; Domb et al, ). The length and width reported here were consistent between sides and sexes but slightly less than previous accounts (Chandler and Kreuscher, ; Kirici et al, ; Philippon et al, ). This difference might be due to variations in measurement methods, different tissue preservation techniques (Martin et al, ), or the variable amount of Haversian fat covering the ligament which may affect the measurements (Chandler and Kreuscher, ).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…There were no significant sex or side differences between any of these ligament dimensions, in spite of ligament injuries being more commonly reported on the right side, and in females (Byrd and Jones, ; Haviv and O'Donnell, ; Amenabar and O'Donnell, ; Domb et al, ). The length and width reported here were consistent between sides and sexes but slightly less than previous accounts (Chandler and Kreuscher, ; Kirici et al, ; Philippon et al, ). This difference might be due to variations in measurement methods, different tissue preservation techniques (Martin et al, ), or the variable amount of Haversian fat covering the ligament which may affect the measurements (Chandler and Kreuscher, ).…”
Section: Discussionsupporting
confidence: 81%
“…In addition, clinical studies consistently show that LHF injuries are more common in females and on the right side, than males and the left side (Byrd and Jones, ; Haviv and O'Donnell, ; Amenabar and O'Donnell, ; Domb et al, ). While occasional ligament absences are found in Europeans (Kaplan, ; Cerezal et al, ; Philippon et al, ), a higher incidence is reported in an Asian population (Tan and Wong, ), suggesting diversity between ethnicities. The reasons for these potential sex and side differences are unknown, and these factors, alongside variation with ethnicity, have not been examined from an anatomical perspective.…”
Section: Introductionmentioning
confidence: 99%
“…In order to reach its maximum tightness, the hip must be flexed, adducted and externally rotated 22,23 , but according to others this occurs in flexion and abduction 24,25 . Philippon et al 26 studied the structural characteristics of the ligamentum teres on 12 human cadaveric models with mean age of 53.6 years and found that the mean ultimate failure load of this ligament is 204 N, showing similar results to another study 27 . During surgery, in order to achieve 10 mm hip joint distraction, a traction force of 110-225 N 28 must be applied and therefore failure should not occur.…”
Section: The Ligamentum Teresmentioning
confidence: 53%
“…The head of the femur is covered by articular cartilage, except for a small ovoid depression situated slightly inferior and posterior to the center of the head called fovea capitis, it serves as a site of attachment of ligamentum teres (9,10).…”
Section: Discussionmentioning
confidence: 99%
“…Few studies focused on the anatomical location of the fovea capitis in the femoral heads, while other researchers studied the anatomical variations of the ligamentum teres and its artery which has its terminal branches piercing the fovea capitis (9)(10)(11)(12)(13). However, it is strange that searching the literature did not reveal any study focusing on the fovea capitis variant configurations and size changes related to the aging process.…”
Section: Introductionmentioning
confidence: 99%